Welcome - Moughan, Paul (New Zealand Science Review, 2010)
A warm welcome to everyone, to the Riddet Institute’s Agri-Food Summit 2010. I would especially like to acknowledge the presence of the Minister for Agriculture, David Carter, Dr Dijkhuizen and the contingent from Wageningen University, and Hans Ramaker from the Dutch Embassy. I note, too, Members of Parliament here – from both sides of the House. Thank you everyone for making the effort to be here.The aim of our summit series is to bring together key New Zealand and international influencers – to discuss and debate topical issues relevant to the agri-food sector. In this our second summit the objective is to ask: Just how well are New Zealand’s research and education resources in agri-food positioned to meet the opportunities that currently exist, and will exist in the future? New Zealand is a producer of protein. As the world’s population continues to grow, so does the demand for food and protein. As developing countries lift their standard of living, the demand for protein increases disproportionately. Further, recent sci-ence points to a higher physiological requirement for protein for humans. This is all good news for New Zealand.In many ways this is our time, and considerable opportunities exist to bring agricultural science, food science, nutritional science, and the new genetics together, to capture the lead as developers of smart knowledge-embedded foods and specialised food ingredients. Being a country distant from our markets, the promise of lower-volume, higher-margin products is particularly relevant. How are we positioned as a nation – in terms of our research capability and our educational facilities – to fully exploit this potential? Can we make the transformational changes that will be needed?We have brought together seven speakers, each highly influential in their own right, who will provide different perspectives on the topic of: ‘Positioning New Zealand’s Research and Education Resources’. It is my great pleasure to call upon the Minister for Agriculture, the Honourable David Carter, to open the Agri-Food Summit 2010.